The Importance of Nutritionists Role in Educating the Community Regarding the Implementation of a Healthy and Balanced Weight-Loss Diet - Putri Novitasari (Journal of Applied Food and Nutrition, 2020)
Obesity is still one of the nutritional problems among Indonesians today. People then want to normalize their nutritional status by adopting certain weight-loss diets. The problem is, recently, some weight-loss diets that have emerged in the community are not following nutritional principles. People with less nutritional knowledge can implement this diet, which will endanger health. The role of nutritionists is very important in providing education to the public about how to carry out a healthy and nutritious weight-loss diet to normalize their nutritional status. This paper discuss the importance role of nutritionists in educating the public regarding the implementation of a healthy and balanced weight-loss diet in the middle of many mistaken types of current weight-loss diets in Indonesia. The study was descriptive and was conducted in Bandung, March 2021. Appropriate nutritional education is the key success to introduce the community to a healthy and balanced diet. Also, other factors determine such as the active role of other health stakeholders in carrying out activities to change attitudes and practices of public health and nutrition.